Immortalized bovine mammary epithelial cells express stem cell markers and differentiate in vitro. (19th June 2016) - Hu, Han; Zheng, Nan; Gao, Haina; Dai, Wenting; Zhang, Yangdong; Li, Songli; Wang, Jiaqi
Abstract: The bovine mammary epithelial cell is a secretory cell, and its cell number and secretory activity determine milk production. In this study, we immortalized a bovine mammary epithelial cell line by SV40 large T antigen gene using a retrovirus based on Chinese Holstein primary mammary epithelial cells (CMEC) cultured in vitro. An immortalized bovine mammary epithelial cell line surpassed the 50‐passage mark and was designated the CMEC‐H. The immortalized mammary epithelial cells grew in close contact with each other and exhibited the typical cobblestone morphology characteristic with obvious boundaries. The telomerase expression of CMEC‐H has consistently demonstrated the presence of telomerase activity as an immortalized cell line, but the cell line never induced tumor formation in nude mice. CMEC‐H expressed epithelial (cytokeratins CK7, CK8, CK18, and CK19), mesenchymal (vimentin), and stem/progenitor (CD44 and p63) cell markers. The induced expression of milk proteins, αS1 ‐casein, β‐casein, κ‐casein, and butyrophilin, indicated that CMEC‐H maintained the synthesis function of the mammary epithelial cells. The established immortalized bovine mammary epithelial cell line CMEC‐H is capable of self‐renewal and differentiation and can serve as a valuable reagent for studying the physiological mechanism of the mammary gland.